(untitled) (Scientific journal of the Fergana State University, 2024)
This article analyzed the pedagogical and psychological possibilities of developing the spiritual and moral qualities of elementary school students during the educational process. In particular, the definitions of Russian and our country’s scientists regarding the theory of education were given. National traditions, rich historical past, humanity, and goodness are taught by them. Based on the ideas of justice, issues of moral improvement were studied. They emphasized that the use of spiritual culture and national values is important in the development of a primary school student. Education is to teach and inculcate manners, manners, and similar forms, to bring a person to adulthood, to raise, to grow. Also, a set of actions aimed at forming and developing a person’s work, manners, and ensuring that he has the qualities necessary for living in society, and manners, character, and virtues inculcated in this way understood. The word education is also derived from the Arabic language and is used in the meaning of teaching, education, imparting knowledge, imparting information. And the process of imparting knowledge, skills and abilities is the main means of preparing a person for life and work. Also, opinions and conclusions are given about the set of information and skills to be acquired and obtained in the fields of science or profession.